Preparation of Biodiesel From Karanja (Pongamia Pinnata) Oil (Journal of Chemical Engineering, 2017)
Biodiesel is a biodegradable, sustainable and clean energy has worldwide attracted renewed and growing interest in topical years, chiefly due to development in biodiesel fuel and ecological pressures which include climatic changes. In this paper, karanja (pongamia pinnata) seed has been studied as a potential source for biodiesel preparation. Karanja oil is extracted from the seed by different methods. Oil properties have been measured by standard methods. Acid catalyzed transesterification, acid catalyzed two-step method and three-step method have been studied for biodiesel preparation from karanja oil. In the three-step method, the first step is saponification followed by acidification to produce free fatty acid (FFA) and finally esterification of FFA to produce biodiesel. In saponification, acidification and esterification reaction, the reaction parameters were optimized. Silica gel was used in both transesterification and esterification to adsorb water, produced in the reaction hence increase the reaction rate. Properties of biodiesel such as specific gravity, FFA, Viscosity, saponification value, iodine value, cloud point, pour point, flash point, cetane index, calorific value etc are measured and compared to conventional diesel fuel and standard biodiesel.Journal of Chemical Engineering, Vol. 29, No. 1, 2017: 24-28